Primary and Secondary Control as Antecedents to the Dark Traits in Predicting Attraction to Hacking Behavior - Amo, Laura; Gaia, Joana; Murray, David; Sanders, G. Lawrence; Sanders, Sean Patrick; Upadhyaya, Shambhu; Wang, Xunyi (Journal of Organizational Psychology, 2023)
The current study examines the relationship between the need for control, the Dark Triad personality traits, and hacking intent. We surveyed 523 individuals using a scenario design and investigated the role of both primary and secondary control as antecedents to Machiavellianism, psychopathy, and narcissism leading to both white- (i.e., ethical) and black-hat hacking interest. Our findings suggest that primary control is a significant antecedent to all three dark personality traits such that a higher intrinsic need for control is positively associated with Machiavellianism, narcissism, and psychopathy. Secondary control, however, has comparatively different effects on dark personality traits, demonstrating a negative effect only on psychopathy. Both Machiavellianism and psychopathy predicted both white- and black-hat hacking interests along with the perceived probability of apprehension. Overall, our findings suggest that primary control drives all three dark personality traits, yet only two of the three dark personality traits – Machiavellianism and psychopathy – are related to hacking interest.